Cereales cancerígenos vida y muerte - Aplica (Revista Universidad de Guayaquil, 1998)
Dr. Rocío Lecaro Vélez is the Coordinator of the Latin American Program for the Fight Against Cancer, and the President of the National Board of Directors of Solca is Dr. Carlos Ferreti Robles, who said he was very concerned because 75% of cases are caused by EXTERNAL AGENTS, including the accursed tobacco. The publication lists 10 basic prevention points, of which #2 is of vital importance for the case we will study below. It states: AVOID excess weight and EAT FRUIT, CEREALS, AND VEGETABLES frequently.